The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/2015jd023100
|View full text |Cite
|
Sign up to set email alerts
|

Determination of equilibrium electron temperature and times using an electron swarm model with BOLSIG+ calculated collision frequencies and rate coefficients

Abstract: Electromagnetic pulse (EMP) events produce low‐energy conduction electrons from Compton electron or photoelectron ionizations with air. It is important to understand how conduction electrons interact with air in order to accurately predict EMP evolution and propagation. An electron swarm model can be used to monitor the time evolution of conduction electrons in an environment characterized by electric field and pressure. Here a swarm model is developed that is based on the coupled ordinary differential equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
(51 reference statements)
0
16
0
3
Order By: Relevance
“…It has been shown previously that the equilibrium electron temperature, U eq , increases appreciably with increasing height for a given electric field, E [ Longmire and Longley , ; Pusateri et al , ]. This means that there is a direct relationship between the equilibrium U eq and the reduced electric field, E / N , where N is the atmospheric number density [ Pusateri et al , ]. It has also been reported that the ionization rate increases significantly with increasing U eq [ Higgins et al , ; Pusateri et al , ].…”
Section: Results and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown previously that the equilibrium electron temperature, U eq , increases appreciably with increasing height for a given electric field, E [ Longmire and Longley , ; Pusateri et al , ]. This means that there is a direct relationship between the equilibrium U eq and the reduced electric field, E / N , where N is the atmospheric number density [ Pusateri et al , ]. It has also been reported that the ionization rate increases significantly with increasing U eq [ Higgins et al , ; Pusateri et al , ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Here it is important to consider a complete description of the time‐dependent conduction electron distribution for the conduction current calculation. Thus, we focus on calculating the conduction current density through the use of a nonequilibrium electron swarm model as presented in Pusateri et al []. We present the final form of the equations solved in the CHAP‐LA code as well as the procedure for integrating the ohmic and swarm conduction electron model into CHAP‐LA in sections 2.1 and 2.2, respectively.…”
Section: Methodology Descriptionmentioning
confidence: 99%
See 3 more Smart Citations